Impact of Parallel Operation of AC Traction Motors on Locomotive Performance - Matej Pacha; Jiri Stepanek (Communications - Scientific letters of the University of Zilina, 2015)
Presented paper deals with common problems of parallel operation of AC traction motors and presents some methods to investigate the basic impacts of the concept. A complex simulation model is introduced as well as results of simulations. Based on the results, a conclusion is made on locomotive performance impact.